Broad-spectrum non-toxic antiviral nanoparticles with a virucidal inhibition mechanism - Cagno, Valeria; Andreozzi, Patrizia; D'Alicarnasso, Marco; Jacob Silva, Paulo; Mueller, Marie; Galloux, Marie; Le Goffic, Ronan; Jones, Samuel T; Vallino, Marta; Hodek, Jan; Weber, Jan; Sen, Soumyo; et al. (Nature materials, 2018)
Viral infections kill millions yearly. Available antiviral drugs are virus-specific and active against a limited panel of human pathogens. There are broad-spectrum substances that prevent the first step of virus-cell interaction by mimicking heparan sulfate proteoglycans (HSPG), the highly conserved target of viral attachment ligands (VALs). The reversible binding mechanism prevents their use as a drug, because, upon dilution, the inhibition is lost. Known VALs are made of closely packed repeating units, but the aforementioned substances are able to bind only a few of them. We designed antiviral nanoparticles with long and flexible linkers mimicking HSPG, allowing for effective viral association with a binding that we simulate to be strong and multivalent to the VAL repeating units, generating forces (∼190 pN) that eventually lead to irreversible viral deformation. Virucidal assays, electron microscopy images, and molecular dynamics simulations support the proposed mechanism. These particles show no cytotoxicity, and in vitro nanomolar irreversible activity against herpes simplex virus (HSV), human papilloma virus, respiratory syncytial virus (RSV), dengue and lenti virus. They are active ex vivo in human cervicovaginal histocultures infected by HSV-2 and in vivo in mice infected with RSV.
Keywords: Herpes Simplex; Respiratory Syncytial Virus Infections; Animals; nanočástice; Antiviral Agents; respirační syncytiální viry; Humans; Mice; Mice, Inbred BALB C; lidský herpesvirus 2; Nanoparticles; Herpesvirus 2, Human; Respiratory Syncytial Viruses; infekce respiračními syncytiálními viry; biomimetické materiály; herpes simplex; antivirové látky; myši inbrední BALB C; zvířata; heparansulfát proteoglykany; Heparan Sulfate Proteoglycans; lidé; Biomimetic Materials; myši